The marketer's handbook : reassessing marketing techniques for modern business - Young, Laurie, 1955- (Chichester, West Sussex, U.K : Wiley, 2011)
"This book has the potential to be a bible for the modern marketer, a reference book that will sit on any marketer's desk or shelf"--
Cover; Title page; Copyright page; DEDICATION; PREFACE; THE BLIND MEN AND AN ELEPHANT; WHAT'S IN AND WHAT'S NOT; THE RATINGS; A; AAR MODEL; ACCOUNT MANAGEMENT; ADVERTISING; "AIDA"; ANSOFF AND HIS MATRIX; AUDIT (THE MARKET AUDIT); B; BEHAVIOURAL INSIGHTS FOR MARKETING; BLUEPRINTING; BOSTON MATRIX; BRANDS; BUSINESS-TO-BUSINESS MARKETING; C; CATEGORY MANAGEMENT; CELEBRITY ENDORSEMENT; CHANNELS OF DISTRIBUTION; CLOSING TECHNIQUES; COMPETITIVE STRATEGY; CONSUMER BEHAVIOUR; CONTACT AUDIT; CORPORATE SOCIAL RESPONSIBILITY (CSR); CULTURAL VARIATIONS; D; DECISION-MAKING UNIT (DMU); DIFFERENTIATION.
Includes bibliographical references (pages 469-477) and index.
Print version record.
Keywords: Marketing; BUSINESS & ECONOMICS -- Sales & Selling; BUSINESS & ECONOMICS -- Distribution; BUSINESS & ECONOMICS -- Marketing -- General; Marketing; Electronic books